Zinc oxide nanorod array as an inhibitory biointerface. (17th September 2018) - Wang, Yongchen; Prox, Jordan D.; Yan, Bingxi; Wu, Yu; Argall, Aaron D.; Guo, Liang
Abstract: Abstract : One-dimensional zinc oxide (ZnO) nanostructure arrays show unique semiconducting, piezoelectric, and wetting properties, and how they interact with cells is critical for their biomedical applications. In this work, we prepare ZnO nanorod arrays (ZnO NRAs) and study their interactions with neonatal rat cardiomyocytes either as a substrate or patch. We find that ZnO NRAs can (1) inhibit cell adhesion and spreading as a substrate and (2) selectively kill underneath cells as a patch. We further identify surface nanomorphology as the dominant factor responsible for the inhibitory effect. These discoveries suggest potential application of ZnO NRAs as a cell inhibitory biointerface.